Fourth pillar in transforming Malaysia's production-based economy towards knowledge-based economy: the role of civil societies [electronic resource] - Nuratika Fatima Mohd Othman, 1988-; Low, Hock Heng, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (2013)
Thesis (Sarjana Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2013